2009
DOI: 10.1097/sla.0b013e3181ac4dfd
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Career Satisfaction Among American Surgeons

Abstract: Burnout is common among American surgeons and is the single greatest predictor of surgeons' satisfaction with career and specialty choice. Additional research is needed to identify individual, organizational, and societal interventions that preserve and promote the mental health of American surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
847
16
45

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 1,118 publications
(948 citation statements)
references
References 59 publications
40
847
16
45
Order By: Relevance
“…Using exact PWBI scores, which provide a way to estimate an individual physician's risk of distress after they complete the PWBI, the likelihood ratio (LR) of low mental QOL ranges from 0.04 (score of 0) to 13.07 (score of 7; Table 2). Assuming a 19 % prevalence of low mental QOL (i.e., the approximate prevalence in the overall 2011 AMA sample 4 and in previous large studies of physicians 17 ) as the pretest probability, the PWBI exact score can lower the post-test probability to < 1 % (score of 0) or raise it to > 75 % (scores of 7).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Using exact PWBI scores, which provide a way to estimate an individual physician's risk of distress after they complete the PWBI, the likelihood ratio (LR) of low mental QOL ranges from 0.04 (score of 0) to 13.07 (score of 7; Table 2). Assuming a 19 % prevalence of low mental QOL (i.e., the approximate prevalence in the overall 2011 AMA sample 4 and in previous large studies of physicians 17 ) as the pretest probability, the PWBI exact score can lower the post-test probability to < 1 % (score of 0) or raise it to > 75 % (scores of 7).…”
Section: Resultsmentioning
confidence: 94%
“…7 The personal accomplishment subscale (PA) of the Maslach Burnout Inventory was used to measure physicians' sense of achievement and meaning in work. 16 Similar to previous physician surveys, [17][18][19] physicians indicating they would "probably" or "definitely yes" choose to become a physician again if they could revisit their career choice were considered to have greater career satisfaction. Additional items from previous physician surveys explored intent to leave current practice within the next 2 years, 8 intent to reduce their clinical hours within 1 year, 8 and self-perceived medical errors in the last 3 months.…”
Section: Study Measuresmentioning
confidence: 91%
“…A relationship between burnout and job satisfaction is established for several types of physicians [1,4,8,10,14,19,26,27], but has been studied less among surgeons treating musculoskeletal conditions. To be able to build and maintain resources to address these issues, it would help to have a better understanding of job satisfaction and burnout among this group of surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…A North American study of trauma surgeons found a 40% prevalence of burnout rated categorically and also found burnout to explain most of the variation in job dissatisfaction. Seventy percent of the surgeons (only 2% of them orthopaedic surgeons) would choose to become a surgeon again [26]. A study of burnout among academic orthopaedic department chairmen found moderate levels of emotional exhaustion and depersonalization [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation